Training And Motivation Affect The Peformance Of Employees In The Bank Frontliner - Reni, Febrina; Rizda, Octaviani; Yulia, Laila; Puteri Anggi, Lubis; nasfi, nasfi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to reveal, first, the effect of training on the motivation of the Bank's front office employees, secondly, the effect of training and motivation on the performance of the Bank's front office employees. Methodology/approach – Path analysis method research with SPSS 13.0, the population of this study are employees of the banking front office operating in the city of Padang Panjang, a sample of 53 respondents, the sample of this research is by means of proportional stratification Cluster Random Sampling. Findings – From the results of this study it is known that training has a significant effect on the work motivation of frontliner employees individually, besides that training and work motivation have a significant influence on the performance of frontliner employees partially simultaneously. Novelty/value – The novelty of this research is to find out the influence of the frontliners who are the spearheads of very influential banking services.